Didáctica del currículum a las estrategias de aprendizaje - Mallart i Navarra, Joan (Revista Española de Pedagogía, 2016)
The main issue we have analyzed in this paper is about the actual content of Didactics and its relationship with the concept of Curriculum, more related to the Anglo-Saxon tradition. We have shown how important both Didactics and Curriculum are in the teaching and learning process. First we have presented the Nordic approach with the participation of several English and American authors. Later on we have analyzed more than 25 studies of General Didactics published in Spanish from 1985 to 1998. This section is focused on the descriptors of Didactics, Curriculum, Methods and Strategies. From our analysis we have concluded how even all of them take care about Curriculum only a few part gives importance to methodology and learning strategies. In the last part we have included some suggestions about the most important contents for teaching in the 21st century based on Spanish and international researches (UNESCO, OCDE, European Community). As a conclusion, we would like to emphasize the idea of how Curriculum and Didactics must take care about the educational contents and also the learning strategies.
Keywords: Revista Española de Pedagogía